2021
DOI: 10.3390/microorganisms9030514
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization of Saccharomyces cerevisiae Sourdough Strains with Cryotolerant Saccharomyces bayanus NBRC1948 as a Strategy to Increase Diversity of Strains Available for Lager Beer Fermentation

Abstract: The search for novel brewing strains from non-brewing environments represents an emerging trend to increase genetic and phenotypic diversities in brewing yeast culture collections. Another valuable tool is hybridization, where beneficial traits of individual strains are combined in a single organism. This has been used successfully to create de novo hybrids from parental brewing strains by mimicking natural Saccharomycescerevisiae ale × Saccharomyceseubayanus lager yeast hybrids. Here, we integrated both these… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 85 publications
0
9
0
Order By: Relevance
“…Among those, S. cerevisiae S-38 has shown physical-chemical, volatile, and sensory characteristics comparable to the commercial strain Safale S-33 (Fermentis, Lesaffre, Marcq-en-Baroeul, France) [83], whereas S. cerevisiae S-42 had higher ethanol content, lower pH, and a higher content of esters [82]. While Catallo et al [85] used a sourdough strain as a parental strain in a de novo hybridisation to obtain a hybrid for lager beer fermentation. The authors reported that the hybrid inherited the ability to produce positive aroma compounds, such as 3-methylbutylacetate, ethyl acetate, and ethyl hexanoate by the sourdough strain, together with the efficient utilisation of maltotriose from the other parental strain [85].…”
Section: Microbesmentioning
confidence: 92%
See 1 more Smart Citation
“…Among those, S. cerevisiae S-38 has shown physical-chemical, volatile, and sensory characteristics comparable to the commercial strain Safale S-33 (Fermentis, Lesaffre, Marcq-en-Baroeul, France) [83], whereas S. cerevisiae S-42 had higher ethanol content, lower pH, and a higher content of esters [82]. While Catallo et al [85] used a sourdough strain as a parental strain in a de novo hybridisation to obtain a hybrid for lager beer fermentation. The authors reported that the hybrid inherited the ability to produce positive aroma compounds, such as 3-methylbutylacetate, ethyl acetate, and ethyl hexanoate by the sourdough strain, together with the efficient utilisation of maltotriose from the other parental strain [85].…”
Section: Microbesmentioning
confidence: 92%
“…While Catallo et al [85] used a sourdough strain as a parental strain in a de novo hybridisation to obtain a hybrid for lager beer fermentation. The authors reported that the hybrid inherited the ability to produce positive aroma compounds, such as 3-methylbutylacetate, ethyl acetate, and ethyl hexanoate by the sourdough strain, together with the efficient utilisation of maltotriose from the other parental strain [85].…”
Section: Microbesmentioning
confidence: 99%
“…Here, we aimed to generate brewing yeast strains with enhanced ability to release volatile thiols during wort fermentation through interspecific hybridization of S. cerevisiae brewing strains with strains of S. uvarum or S. eubayanus . Interspecific hybridization has been used extensively for brewing yeast strain development in the past decade [2830, 55, 56]. It allows for combining traits from diverse parent strains, can be performed without any genetic engineering, and hybrids may in some cases exhibit hybrid vigour, where they outperform the parent strains in certain traits [7].…”
Section: Discussionmentioning
confidence: 99%
“…Spore viability was determined by asci dissection and monospore clone constitution as previously reported [ 46 ], according to the following equation: Spore Viability % = (n° of vital monosporic cultures/n° of dissected spores) × 100, …”
Section: Methodsmentioning
confidence: 99%
“…For each strain, at least eight asci were dissected. Both wild strains and their monospore derivatives were genotyped for the MAT locus according to Catallo et al [ 46 ]. Strains BY4742 and BY4743 ( Table 1 ) were used as positive MATα and MATα / MAT a controls, respectively.…”
Section: Methodsmentioning
confidence: 99%